Wheat sowing depth in the cerrados region. I. Seedling emergence - Silva, Dijalma Barbosa da (Pesquisa Agropecuaria Brasileira, 1992)
An adequate sowing depth is a fundamental factor in seedling emergence. The objective of this study was to evaluate the effect of the sowing depth of wheat (Triticum aestivum L.) on seedling emergence in the Cerrados region of Brazil. Three experiments were conducted at Planaltina, DF, in 1990. The treatments were four sowing depths (2.0; 5.0; 8.0 and 11.0 cm) and six wheat cultivars (BH 1146; BR 16; BR 26; BR 10; BR 33 and Candeias) which are recommended for this region. The increase in sowing depth caused an increase in seedling emergence up to the depth of 5.8 cm, decreasing afterwards. Except in one of the experiments at sowing depth of 11.0 cm, the seedling emergence was retarded. The cultivars behaved differently with respect to the evaluated parameters.